Vitamin C Rescues in vitro Embryonic Development by Correcting Impaired Active DNA Demethylation - Chu, Meiqiang; Yao, Fusheng; Xi, Guangyin; Yang, Jiajun; Zhang, Zhenni; Yang, Qianying; Tian, Jianhui; An, Lei (Frontiers in Cell and Developmental Biology, 2021)
Dynamic epigenetic reprogramming during mammalian early development is the prerequisite for normal embryogenesis, and erroneous epigenetic reprogramming during the critical developmental window are linked to various short- or long-term complications. Among these, a wave of genome-wide DNA demethylation that occurs during preimplantation development, is an essential epigenomic event for establishing full developmental potential. Despite its importance, this process is prone to be disrupted due to environmental perturbations such as manipulation and culture of embryos during in vitro fertilization (IVF), and thus leading to epigenetic errors. However, since the first case of aberrant DNA demethylation reported in IVF embryos, its underlying mechanism remains unclear and the strategy for correcting this error is unavailable in the past decade. Herein, using mouse and bovine IVF embryos as the model, we reported that TET-mediated DNA active demethylation, an important contributor to the postfertilization epigenome reprogramming, was impaired throughout preimplantation development. Focusing on modulation of TET dioxygenases, we found vitamin C and α-ketoglutarate, the important co-factors for stimulating TET enzymatic activity, were synthesized in both embryos and the oviduct during preimplantation development. Accordingly, the impaired DNA active demethylation can be corrected by incubation of the IVF embryos with vitamin C, and thus improving their lineage differentiation and developmental potential. Together, our data not only provides a promising approach for preventing or correcting IVF-associated epigenetic errors, but also highlights the critical role of small molecules or metabolites form maternal paracrine in finetuning embryonic epigenomic reprogramming during early development.